SPIRITUALITAS CALVIN SEBAGAI SPIRITUAL FORMATION MAHASISWA TEOLOGI - Obet Nego (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
Students in theology schools must have a clear and determined calling. Often this commitment fades because the knowledge of God only happens in the mind, not in the heart. Therefore we need teaching that can invite them back to deepen their commitment to God. Therefore, in addition to intellectual abilities, mature spirituality, is considered an absolute requirement for theology students to become servants of God who are ready to serve. Success in ministry that demands a complete spiritual figure, requires a servant of God to set an example in his Bible, moral, and spiritual knowledge. Since it was in the formation on campus, it was hoped that theology students would have to realize the importance of a Bible-based spirituality, God's word. Therefore, this paper aims to discuss Calvin's Spirituality as a Theological Formation of Spiritual Students.